Red Light/Green Light, a Dual Fluorescent Protein Reporter System To Study Enhancer-Promoter Specificity in Drosophila. Issue 3 (1st March 2020) - Camino, Eric M; Weinstein, Micheal L; List, Mary P; Vellky, Jordan E; Rebeiz, Mark; Williams, Thomas M
Abstract: Enhancers activate gene transcription in spatial and temporal patterns by interactions with gene promoters. These elements typically reside distal to their target promoter, with which they must interact selectively. Additional elements may contribute to enhancer-promoter specificity, including remote control element sequences within enhancers, tethering elements near promoters, and insulator/boundary elements that disrupt off-target interactions. However, few of these elements have been mapped, and as a result, the mechanisms by which these elements interact remain poorly understood. One impediment is their method of study, namely reporter transgenes in which enhancers are placed adjacent to a heterologous promoter, which may circumvent mechanisms controlling enhancer-promoter specificity and long-range interactions. Here, we report an optimized dual reporter transgene system in Drosophila melanogaster that allows the simultaneous comparison of an enhancer's ability to activate proximal and distal fluorescent reporter genes. Testing a panel of fluorescent transgenes in vivo, we found a two-protein combination that allows simultaneous measurement with minimal detection interference. We note differences among four tested enhancers in their ability to regulate a distally placed reporter transgene. These results suggest that enhancers differ in their requirements for promoter interaction and raise important practical considerations when studying enhancer function.